Analisis Gaya Belajar (Learning Modalities) Siswa dalam Pembelajaran Berdiferensiasi di Kelas 4 SD N Pesantren - munawaroh, faridatul (Jurnal Gentala Pendidikan Dasar, 2023)
This study was conducted with the aim of obtaining an overview of the learning style profile of fourth grade students of SD N Pesantren. The purpose of the results of this research is for initial assessment in differentiated learning that will be applied to the class. This research uses qualitative descriptive research. Survey with a self-developed learning style questionnaire from the indicators described by Bobby De Porter is the method used in this study to obtain data from research subjects. There are three learning styles studied, namely visual, auditory and linesthetic learning styles. Based on the data analysis in the class, the majority of students have a visual learning style tendency. However, there are no students who only depend on one learning style, but of the three learning styles there are more dominant than others. Differentiated learning aims to accommodate the diversity of student needs. This study was conducted by researchers in class IV to map students' learning needs which then became a guideline for planning differentiated learning.